Conférence: «Droit et féminisme - Rencontre entre deux champs» - Institut de recherches et d'études féministes; Réseau Québécois en études féministes (2018)
Avec Rachel Chagnon, membre de l'Institut de recherches et d'études féministes et professeure au Département des sciences juridiques.
Keywords: amériques; approches et analyses; discipline; discours dominant; droit; droits des femmes*; europe; féminisme décolonial; histoire du féminisme; intersectionnalité; inégalités; militance; mouvements des femmes*; rapports sociaux de sexe; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; sciences juridiques; sociologie; système colonial; systèmes d'oppressions; thématiques

Radical reproductive justice: Foundation, theory, practice - Ross, Loretta; Roberts, Lynn; Derkas, Erika; Peoples, Whitney; Bridgewater Toure, Pamela (Feminist press, 2017)
Expanding the social justice discourse surrounding "reproductive rights" to include issues of environmental justice, incarceration, poverty, disability, and more, this crucial anthology explores the practical applications for activist thought migrating from the community into the academy. Radical Reproductive Justice assembles two decades’ of work initiated by SisterSong Women of Color Health Collective, creators of the human rights-based “reproductive justice” framework to move beyond polarized pro-choice/pro-life debates. Rooted in Black feminism and built on intersecting identities, this revolutionary framework asserts a woman's right to have children, to not have children, and to parent and provide for the children they have.
Keywords: afro-féminisme; approches et analyses; discipline; droit; droits des femmes*; intersectionnalité; justice reproductive; justice sociale; maternité; militance; santé; science politique et droit; sciences humaines; sociologie; thématiques

Kimberlé Crenshaw: The urgency of intersectionality | TED Talk - Crenshaw, Kimberlé (TedTalk, 2016)
Now more than ever, it's important to look boldly at the reality of race and gender bias -- and understand how the two can combine to create even more harm. Kimberlé Crenshaw uses the term "intersectionality" to describe this phenomenon; as she says, if you're standing in the path of multiple forms of exclusion, you're likely to get hit by both. In this moving talk, she calls on us to bear witness to this reality and speak up for victims of prejudice.
Keywords: activisme; afro-féminisme; approches et analyses; com5170; cours; discipline; droit; droits civiques; droits des femmes*; droits humains; féminisme afroaméricain; histoire et politique; intersectionnalité; justice sociale; militance; premier cycle; science politique et droit; thématiques

Sexualized Violence and Colonialism: Reflections on the Inquiry into Missing and Murdered Indigenous Women - Razack, Sherene (Canadian Journal of Women and the Law, 2016)
Introduction to the special isuue of the Canadian Journal of Women and the Law on the "Missing and Murdered Indigenous Women Conference".
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; discipline; droit; droits des femmes*; féminicide; intersectionnalité; justice sociale; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; science politique et droit; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Prison sexual abuse: Race, gender, and the rule of law - Buchanan, Kim (Columbia University, 2010)
In this dissertation, I argue that the exemption of prisons from the rule of law fosters abusive institutional practices that reveal the race and gender dynamics of sexual abuse in prison and in the outside world. The first article, Beyond Modesty: Privacy in Prison and the Risk of Sexual Abuse, shows that Fourth Amendment privacy offers little protection against the cross-gender searches and surveillance that expose women prisoners to sexual abuse by male guards. It proposes a reinterpretation of Fourth Amendment privacy that would recognize a constitutional right to be free from the fear, risk and reality of prison sexual abuse. The second article, Impunity: Sexual Abuse in Women's Prisons, shows that an edifice of constitutional, statutory and common-law rules confers near-complete institutional immunity against nearly all prisoner claims of custodial sexual abuse. These immunity rules parallel those of historical status regimes which excluded low-status litigants from courts on the basis of race and gender, such as civil death, slavery, segregation and the common law of marriage and rape--with similar results: low-status women of color are exposed to systematic and institutionalized sexual abuse, and are prevented from seeking protection or redress from the courts. The third article, Our Prisons, Ourselves: Race, Gender and the Rule of Law, develops these insights in men's prisons. In the absence of enforceable external rules, staff and administrators often adopt a gendered practice of institutional governance that requires prisoners to prove their manhood by fighting, and penalizes unmanly men by allowing others to rape them. These unlawful gendered practices are obscured by a false but powerful racialized narrative: most people inside and outside prison believe, inaccurately, that prison rape is mainly black-on-white. By casting sexual violence as a "complex and intractable" race relations problem for which administrators are not to blame, the racial narrative bolsters the rationale for exempting prison administration from the rule of law. Thus the perception (and reality) of unchecked prison violence supplies a reason for courts not to interfere with the unlawful institutional policies that foster it.
Keywords: approches et analyses; criminologie; discipline; droit; genre; intersectionnalité; mémoires/thèses; racisme; ressource en ligne; science politique et droit; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexuelles